(untitled) (Research, Society and Development, 2021)
This work aimed to elaborate the zoning of the hydro-territories of the Metropolitan Region of Belém, identifying the areas of the greatest threat to water sustainability in the forming hydrographic basins. The methodology used the association between the spatial distribution of the drainage network, the digital elevation model, the rainfall, and the expansion of urban infrastructure and road design, to generate integrated zoning. The results indicated that the areas with a better tendency for expansion in the RMB are in topographic dividers. Most of the region (64.70%) is located in areas of greater rainfall and runoff, with variable occupation density, with a predominance of low-density areas, alternating with regions of high local concentration. This result comprises the unit called the Insular Area and the one that covers the Canals of Foz (about 33% of the total area of RMB). The most impacted basins are Drainage Channels I (70.57%), Igarapé São João (52.26%), Caraparu River (54.42%), Benfica River (73.33%), Paricatuba River (97.07%), and Araci River (53.02%); in these, the forms of land use predominate over local water systems, compromising the municipalities of Benevides (79.57%) and Marituba (67.43%). Therefore, the evolution of urban space in the RMB, its environmental consequences, and the water future potential depend on the territory and water resources management associated.